Estimation of genetic parameters for chosen udder traits of different dairy ewes - MAKOVICKÝ, PAVOL; MAKOVICKY, PETER; MARGETÍN, MILAN; NAGY, MELINDA (The Indian Journal of Animal Sciences, 2019)
Morphology of udder in ewes in one experimental herd was examined on the basis of linear evaluation (7 traits; 9 points scale; 1145 data for each trait) and exact measurements of udder (6 parameters; 1055 measurements at each trait) were taken. Estimation of covariance components and genetic parameters were done using REML and BLUP-AM (VCE 4.0 package) for 7 traits (linear evaluation) or 6 traits (udder measurements) . Heritability coefficients for individual traits of linear evaluation varied from 0.090–0.294. Heritability coefficient (h2) for teat position was 0.242, 0.275 for teat size , and 0.294 for cistern depth, which is related to teat position. The highest value of genetic correlation (rg=0.980) was found between cistern depth and teat position. Negative genetic correlation was detected between teat position and teat size (–0.381), and teat position and udder cleft (–0.404). Heritability coefficients and genetic correlations of exact measurements of udder were comparable with traits of linear evaluation. For the parameter, udder length and rear udder depth, the detected band-measures were h2 = 0.219 or 0.223. Highest h2 was found for cistern depth (0.480), teat length (0.358) and teat angle (0.290) similar to linear evaluation.